Analisis Kebijakan Kota Layak Anak di Kota Banda Aceh Menurut Indikator Kota Layak Anak - Asyiatun Nabila; Saddam Rassanjani; Afrijal Afrijal (Institut Pemerintahan Dalam Negeri, 2024)
Child-Friendly City (KLA) is a strategic policy that aims to ensure the fulfillment of children’s rights through synergy between government, society, and the business world. This study aims to analyze the implementation of the KLA policy in Banda Aceh City with a focus on seven institutional indicators as stipulated in the Regulation of the Minister of State for Women’s Empowerment and Child Protection of the Republic of Indonesia Number 12 of 2011 concerning Indicators of Child-Friendly Districts/Cities. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. Informants consist of government officials, community leaders, and representatives of relevant community institutions. The results of the study indicate that Banda Aceh has not fully achieved Child-Friendly City status. Several institutional indicators, such as special budget allocation and involvement of community institutions, have been implemented, but are not optimal. The Regional Action Plan for Child-Friendly City is not yet available, and involvement of the business world is still limited. At the village level, understanding of the KLA concept is still low, so that policy implementation is not evenly distributed. It is necessary to strengthen the synergy between the City Government and villages, special budget allocation, and involvement of the business world through the establishment of the Indonesian Child-Friendly Company Association (APSAI). With these steps, it is hoped that the implementation of KLA can be accelerated, so that the fulfillment of children's rights in Banda Aceh can be realized comprehensively.